Effect of CNT embedding angle on tensile behavior and dislocation mechanisms in magnesium matrix composites: a molecular dynamics study - Chentong Zhao; Jiming Zhou; Yunfeng Bai; Kang Yun; Lehua Qi (Results in Physics)
This study explores the influence of CNT embedding angles on the tensile behavior and dislocation evolution of CNT/Mg composites using molecular dynamics simulations. The results reveal that CNTs aligned parallel to the tensile loading direction significantly enhance the composite’s tensile strength and stiffness, with the maximum tensile strength of 6.07 GPa and a Young’s modulus of 90.01 GPa at 0° embedding. As the embedding angle increases, the tensile strength decreases, while the Young’s modulus exhibits non-monotonic variations. At low angles, CNTs enable efficient load transfer, thereby reinforcing the matrix, while at larger angles, their load transfer efficiency diminishes, leads to stress localization and potential interface debonding. The dislocation evolution analysis shows that CNTs serve as dislocation traction at small angles, but at higher angles, they act as dislocation obstacles, leading to dislocation entanglement and local damage. These findings highlight the complex interplay between load transfer efficiency and dislocation mechanisms, offering insights for optimizing CNT orientation in composites to enhance mechanical performance. Future studies should focus on improving interface adhesion and tailoring CNT distributions for maximum strengthening effects.